Covid 19 en Oaxaca: respuestas etno-culturales ante la crisis sanitaria - Barabas, Alicia M. (Comparative Cultural Studies: European and Latin American Perspectives, 2020)
This paper try to give an ethnographical look over a positive exemple of collective actions address by originals peoples of Oaxaca state, in Mexico, to prevent and overcome the pandemic Covid19. I shall present with detail the case of Santiago Comaltepec, a municipality at the Sierra Norte inhabited by chinantec indians; what they think, the decisions they make and the actions they take to confront it.The autonomous community responses are posible beacause the exercise of traditional forms of election and government called Internal Normative Systems at the Constitution of Oaxaca State.